The Stromal Cell-derived Factor-1/CXCL12 3’A-gene Polymorphism is Related to the Increased Risk of Coronary Artery Disease: A Systematic Review and Meta-analysis - Prabawa, I Putu Yuda; Lestari, Anak Agung Wiradewi; Muliarta, I Made; Mardhika, Putu Eka; Pertiwi, Gusti Ayu Riska; Bhargah, Agha; Manuaba, Ida Bagus Amertha Putra; Artha, Made Junior Rina; Rina, I Ketut; Rampengan, Starry Homenta (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Single-nucleotide polymorphism in the stromal cell-derived factor-1 (SDF-1)/CXCL12 gene had been associated with an increased risk of coronary artery disease (CAD). However, several published studies have shown inconsistent results. AIM: A meta-analysis was assessed to evaluate the association between SDF-1 3’A-gene polymorphism and CAD in the literature. METHODS: A systematic review was conducted in accordance with PRISMA guidelines and adhering to the Cochrane Handbook for Systematic Reviews. The literature search strategy was carried out on April 3, 2019, from PubMed, EBSCO, Google Scholar, and DOAJ during 2013–2018 period using various keywords related to SDF-1, CXCL12, polymorphism, and CAD. Original data from the group, case-control study, English full-text, and DNA polymorphism assessment using polymerase chain reaction were enrolled. Gene polymorphism in A-base nucleotide among patients with CAD and healthy subjects were evaluated. All data were analyzed using Review Manager 5.3 (Cochrane, Denmark) for meta-analysis. RESULTS: Five eligible studies extracted for data analysis (2013–2018) based on the assessment of 2-independent reviewers. Several studies have been excluded due to irrelevant criteria evaluated. A significant result was found between SDF-1 3’A gene polymorphism with the increased risk of CAD in the overall effect evaluation using a fixed-effects model (odds ratio [OR]: 2.02; 95% confidence interval 1.54-2.65; I2: 34%; p<0.001) on the forest plot. CONCLUSION: Our meta-analysis suggests that gene polymorphism in A-base nucleotide of SDF-1/CXCL-12 was associated with the susceptibility of CAD. However, a bigger-scale and well-design of case-control study should be conducted to clarify these conclusions.